Adolescents and Internet Cafes - Demır, Yasın; Kutlu, Mustafa (My University, 2018)
The purpose of this study was to examine the levels of aggression of adolescents playing game in the internet cafes located in the city of Elazig in terms of different variables (gender, academic achievement, and most played game type). The universe of study consists of high school students playing game in the internet cafes in the city of Elazığ in Turkey. The sample of study consists of 119 females, and 268 males, totally 387, high school students playing game in the internet cafes. As the research data collection tool, Aggression Scale developed by Tuzgol were used. According to the findings obtained from the study, the levels of agression in male students are higher than female students, the levels of agression in students having low levels of academic achievement are higher than the levels of agression in students having high levels of academic achievement, the levels of agression in the students who play war and violent games are higher than the levels of agression in the students who play different types of games.
Keywords: Eğitim; Eğitim Araştırmaları; Psikoloji; Davranış Bilimleri